Evaluation of growth responses of CassavaTreated with Pleurotus tuber-regiumSpent Mushroom Substrate WaterExtract to Elicit Disease Resistance. - S.E , Okere; A.E , Ataga; E.N , Elenwo; I.I , Ekpe (African Journal of Education,Science and Technology (AJEST), 2016)
This paper investigatedthe effect of Pleurotus tuber-regiumspentmushroom substrate water extract on the growthof cassava generatedthrough meristem tissue culture.The cassava plantlet (tms 98/0505) were generated at the Tissue Culture Laboratory of Biotechnology unit,National Root Crop Research Institute ,Umudike Umuahia Abia State before they were transfered to the screen house of the Faculty of Agriculture Teaching and Research Farm, University of Port Harcourt, RiversState.The water extract was applied on the cassavato elicit disease resistance after 4 months of culturing in a nutrient medium.The treatments for this investigation comprised of T1; Pleurotus tuber-regium water extract spent mushroom substrate (PTWESMS), T2;Pleurotus tuber-regiumautoclaved water extract spent mushroom substrate (PTAWESMS) andT3; the control.The experiment was laid outin a completely randomized design with 3 replicates.The data generated were subjected to analysis of variance(ANOVA).Means were separated using Fishers Least SignificantDifference at P=0.05. The results obtained revealedthatthere was no significant differencewhenthe different treatments were compared withe the control and when the treatments were compared with one another in theirmean plant height, meannumber of leaves, mean number ofnode and meanleaf area. However, the stem diameterandnumber of internode were significantly different. The result also revealed a significantly positive corelation (r) between plant height andstem diameter and a positivecorrelation between the number ofinternodesand leaf area and had a negativecorrelationbetweennumber of leaves and number of nodes. Nnumber of leavescorrelatednegatively with plant height, stem diameter and leaf area and corelated positvely with number of internode and number of nodes. Again, the stem diameter had a significantlypositive correlationwith plant height, number of internode, and leaf area and a positive relationship with Number of node. Number of internode correlates positively with all the parameters evaluated. Number of nodes related positively with number of leaves, stem diameter and number of internode while a negative correlationwith plant height andleaf area was observed. This could possibly be the first account of this investigation.